2013
DOI: 10.1364/ao.52.007094
|View full text |Cite
|
Sign up to set email alerts
|

Optimal fringe angle selection for digital fringe projection technique

Abstract: Existing digital fringe projection (DFP) systems mainly use either horizontal or vertical fringe patterns for three-dimensional shape measurement. This paper reveals that these two fringe directions are usually not optimal where the phase change is the largest to a given depth variation. We propose a novel and efficient method to determine the optimal fringe angle by projecting a set of horizontal and vertical fringe patterns onto a step-height object and by further analyzing two resultant phase maps. Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…The principle of touch detection is based on the triangulation [30] in our interactive projection system. A linear-scanning method is proposed to detect the triangulation of the finger and its shadow without separating the hand from its shadow, which can increase the robustness of the system and reduce the computation cost.…”
Section: Touch Detectionmentioning
confidence: 99%
“…The principle of touch detection is based on the triangulation [30] in our interactive projection system. A linear-scanning method is proposed to detect the triangulation of the finger and its shadow without separating the hand from its shadow, which can increase the robustness of the system and reduce the computation cost.…”
Section: Touch Detectionmentioning
confidence: 99%
“…Figure 4 shows an example process of determining the optimal fringe angle under a particular system setup. As introduced in [29], the optimal fringe angle of a particular system setup can be determined by measuring a step-height object, shown in Fig. 4(a).…”
Section: B Least Squares Phase-shifting Algorithmmentioning
confidence: 99%
“…However, the methods belonging to this category are not trouble free since they all require horizontal and vertical patterns. According to Wang and Zhang [29], once the system is set up, there exists an optimal fringe angle for pattern projection which is most sensitive to depth variation, while its orthogonal fringe direction is regarded as the worst angle, which has almost no response to depth variation. In practical experiments, either horizontal or vertical patterns are used in most cases.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is easy to obtain a fringe angle of zero by projecting vertical fringe patterns, it is not equal to the systematic angle. Hence, the fringe patterns need to be projected at an optimal angle to ensure that the fringe angle is equal to the systematic angle, just as Wang and Zhang did [14].…”
Section: A Triangulation Principlementioning
confidence: 99%
“…Wang and Zhang made some research and indicated that simply projecting horizontal or vertical fringe patterns is not the best option to obtain optimal sensitivity to object depth variations. They proposed a method to determine the optimal fringe angle by projecting a set of horizontal and vertical fringe patterns onto a step-height object [14]. To our knowledge, the mathematical analysis of the optimal fringe angle is still lacking in the systems based on either the triangulation principle or the stereovision principle.…”
Section: Introductionmentioning
confidence: 99%